La partería tradicional (2018)
Introduction: Traditional midwives support humanized delivery, which allows women in labor to control the situation and make their own decisions. Objective: To describe the practices of traditional midwifery in three regions of Magdalena Department, Colombia. Methods: Cross-sectional descriptive study, with a quantitative approach, developed with 15 midwives from the municipalities of Santa Marta, Ariguaní, and Fundación, Magdalena Department. The data were collected using a structured and validated questionnaire, applied in the first semester of 2016. The sample was taken at convenience, given the researchers' level of accessibility with the midwives. Five midwives from each population could be obtained, for a total of 15. The quantitative data were analyzed using descriptive statistics (percentage and average distribution). Results: 54% were at age 50-80 years, 80% lived in rural areas, 53% had 30-60 years of experience as midwives, all are women (100%) and knew how to read and write, 93% spoke Spanish, only 7% spoke the native language, 47% learned how to assist births by family tradition, 25% learned by themselves, 20% learned how to assist births through another person, and 8% learned by means of a training course. Conclusion: Midwifery in this region continues to be transferred from generation to generation, having traditional practices, such as the use of intakes after delivery care. © 2018 Revista Cubana de Enfermería.